Cloud Robotics: Its Industrial Automation Implementation And Challenges (International Journal of Engineering and Computer Science, 2017)
Since the cloud computing is easily and widely available and robots along with its automation system have been at the front of research with majority of systems still operating on the basis of onboard computation and memory management , it is wise to develop a system which allows integration of robotic services with cloud services. The cloud robotic architecture leverages the combination of a cloud formed by machine to machine (M-2- M) communication among participating robots and an infrastructure cloud enabled by machine to cloud communications(M-2-C). Success in cloud robotics implementation will also help in future robotics application to evolve more as one of the standard service accessible through the cloud similar to the applications of other domain which were based on cloud computing. The aim of this paper is to provide a better understanding and implementation of cloud robotics in industries using parallel grid computing and cloud architecture.